Crimean-Congo haemorrhagic fever (CCHF) in Senegal: Are we on the verge of another outbreak?. (November 2022) - Ghosh, Shankhaneel; Das, Soumyajit
Abstract: The recent outbreak of Crimean Congo haemorrhagic fever (CCHF), a tick-borne illness with a high fatality rate, in Senegal is due to an arbovirus known as Crimean-Congo haemorrhagic fever virus (CCHFV). CCHF is endemic in a number of areas in Asia, Africa, and Europe. The present CCHF outbreak, however, is severe and requires quick treatment in order to prevent and contain it before it spreads further. This letter provides an overview of the most recent research on the CCHF outbreak in Senegal, along with information on the main traits of this dangerous disease, advancements in the creation of vaccines and therapies, and efficient prevention and control methods.